STUDENTS' PRACTICES AND PERCEPTIONS IN USING DUOLINGO FOR ENGLISH LEARNING: A DESCRIPTIVE QUALITATIVE STUDY AT SMP NEGERI 25 BULUKUMBA - Raodatul Jannah; Samtidar Samtidar; Chaerul Fadlan Saud (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2026)
This study aims to describe students' practices and perceptions in using the Duolingo application for English learning at SMP Negeri 25 Bulukumba. This research employed a descriptive qualitative approach involving eight eighth-grade students selected through purposive sampling. Data were collected through observation checklists and semi-structured interviews. Observation was conducted to directly examine students' learning practices when using the Duolingo application, while interviews were used to explore students' practices and perceptions in greater depth. The data were analyzed using the stages of data reduction, data display, and conclusion drawing, as outlined in the analytical model proposed by Miles, Huberman, and Saldana (2014). The findings revealed that students' learning practices aligned with the three phases of Self-Regulated Learning (Zimmerman, 2002): forethought, performance, and self-reflection. Students actively set learning goals, consistently used Duolingo features, engaged in various learning activities, and evaluated their learning progress. Perceptions, as indicated by the Technology Acceptance Model (Davis, 1989), indicated that students had positive attitudes toward the Duolingo application. They considered it useful in supporting the development of vocabulary, grammar, and reading skills. In addition, they found the application easy to use, flexible, and engaging, thanks to its user-friendly interface and gamification features. Overall, the findings indicate that Duolingo supports students' independence, motivation, and the effectiveness of English learning. The application has the potential to serve as an innovative mobile-assisted language learning tool that enhances English instruction at the junior high school level.Keywords: Duolingo, learning practices, student perceptions, Self-Regulated Learning, Technology Acceptance Model.